2017
DOI: 10.1063/1.5005169
|View full text |Cite
|
Sign up to set email alerts
|

Dielectric, magnetic, ferroelectric, and Mossbauer properties of bismuth substituted nanosized cobalt ferrites through glycine nitrate synthesis method

Abstract: CoFe2-xBixO4 nanoferrites with x = 0, 0.05, 0.1, 0.5, and 1.0 have been synthesized by the glycine nitrate process. The present study investigates the effect of Bi3+ substitution on the microstructural, dielectric, ferroelectric, magnetic, and Mossbauer properties of CoFe2O4 nanoparticles. The X-ray diffraction technique was used to confirm the phase purity and estimate the crystallite size which revealed the formation of a secondary phase when Bi3+ concentration exceeds x = 0.5. Transmission electron microsco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 51 publications
(20 citation statements)
references
References 51 publications
1
19
0
Order By: Relevance
“…Polycrystalline ferrites were classified as good magnetic semiconductors having low electrical conductivity and eddy currents, that play an essential role in various technological applications from microwave to radio wave frequencies [1,2]. Ferrites also belong to a special class of ceramic materials that exhibit ferromagnetic nature at room temperature [3]. Among the several spinel ferrites, MFe2O4 (M=Zn, Mn, Co, Ni), ZnFe2O4 exhibits particularly intriguing features due to the diamagnetic nature of Zn 2+ and the ferrous behavior of Fe (Fe 2+ and Fe 3+ ) ions, which have highly physical and chemical stability [4].…”
Section: Introductionmentioning
confidence: 99%
“…Polycrystalline ferrites were classified as good magnetic semiconductors having low electrical conductivity and eddy currents, that play an essential role in various technological applications from microwave to radio wave frequencies [1,2]. Ferrites also belong to a special class of ceramic materials that exhibit ferromagnetic nature at room temperature [3]. Among the several spinel ferrites, MFe2O4 (M=Zn, Mn, Co, Ni), ZnFe2O4 exhibits particularly intriguing features due to the diamagnetic nature of Zn 2+ and the ferrous behavior of Fe (Fe 2+ and Fe 3+ ) ions, which have highly physical and chemical stability [4].…”
Section: Introductionmentioning
confidence: 99%
“…All chemicals used were purchased from Sigma–Aldrich with 99% purity. The detail experimental procedure is illustrated in our earlier publications . The final obtained powder was then calcined at 600 °C for 3 h. CFHO synthesized powder samples were X‐ray examined by Rigaku Ultima‐IV X‐Ray Diffractometer (XRD) (Cu‐K α radiation, k = 1.54 Å).…”
Section: Methodsmentioning
confidence: 99%
“…Savunthari and Shanmugam (2019) revealed that the incorporation of bismuth in zinc ferrite resulted in a decrease in crystallite size, saturation magnetisation and band-gap energy. Moreover, the tendency of bismuth ion for both the octahedral and tetrahedral sites occupancy with higher affinity for octahedral sites was anticipated by various researchers (Routray et al, 2017;Gore et al, 2017). It is readily notified in the literature that bismuth substituted nanoferrites have been employed as potential catalysts in wide-ranging reactions (Ren et al, 2016;Fesharaki et al, 2017;Kiran and Sumathi, 2017;Sumathi and Lakshmipriya, 2017).…”
Section: Introductionmentioning
confidence: 93%
“…The magnetic nature of bismuth‐doped nanoferrites endures their wide potential for memory devices and magnetic recording applications for data storage (Gore et al , 2015; Panda et al , 2015; Suresh and Vijaya, 2016; Gore et al , 2017; Routray et al , 2019). Many research cohorts have examined the electrical, magnetic, structural and optical characteristics of bismuth incorporated nanoferrites (Gore et al , 2015; Routray et al , 2017; Savunthari and Shanmugam, 2019). Panda et al (2015) observed the modification in electrical properties including increased resistivity and reduced dielectric loss with the incorporation of bismuth into cobalt ferrite lattice.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation